2020
DOI: 10.3386/w27814
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Disrupts Sleep

Abstract: Although there is a substantial literature indicating that unemployment and joblessness have profound adverse impacts on individuals' health and wellbeing, there is relatively little evidence of their impact on sleep. Using data for over 3.5 million individuals in the United States over the period 2006-2019 from the Behavioral Risk Factor Surveillance System (BRFSS) survey series we show sleep disruption patterns that vary by labor market status. We look at sleep measured by hours in a day and days in a month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…There are inverted U‐shapes for nine of the 12 components based on differentiating with respect to age and solving for the minima obtained using a quadratic in age. Interestingly, sleeplessness has an inverted U‐shape consistent with the findings of Blanchflower and Bryson (2020) who found that sleep duration in the USA followed a U‐shape in age.…”
Section: Empirical Evidence On Midlife Peak In Well‐being In Scotland and England 2008–2019supporting
confidence: 87%
See 1 more Smart Citation
“…There are inverted U‐shapes for nine of the 12 components based on differentiating with respect to age and solving for the minima obtained using a quadratic in age. Interestingly, sleeplessness has an inverted U‐shape consistent with the findings of Blanchflower and Bryson (2020) who found that sleep duration in the USA followed a U‐shape in age.…”
Section: Empirical Evidence On Midlife Peak In Well‐being In Scotland and England 2008–2019supporting
confidence: 87%
“…There is a hill‐shape in anti‐depressant use which maximizes in the mid‐40s in European countries (Blanchflower & Oswald, 2016). There are U‐shapes in sleep duration (Blanchflower & Bryson, 2020). The U‐shape pattern in midlife even extends beyond humans to apes (Weiss et al., 2012).…”
Section: Literature On a U‐shape In Age In Well‐beingmentioning
confidence: 99%
“…New Mexico also re-implemented a two-week SAH order that was in effect from November 16 through November 30, 2020. While such policies lower the transmission rate [1][2][3], reduced economic activity and social interactions due to the lockdown have also resulted in economic and psychological costs [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a hill-shape in anti-depressant use which maximizes in the mid-40s in European countries (Blanchflower and Oswald, 2016). There are U-shapes in sleep duration (Blanchflower and Bryson, 2020). The Ushape pattern in mid-life even extends beyond humans to apes (Weiss et al, 2012).…”
Section: Literature On a U-shape In Age In Well-beingmentioning
confidence: 99%